Effect of targeted nutrient supplementation on physical activity and health-related quality of life in COPD: study protocol for the randomised controlled NUTRECOVER trial. Issue 3 (16th March 2022) - Beijers, Rosanne JHCG; van Iersel, Lieke E J; Schuurman, Lisanne T; Hageman, Robert J J; Simons, Sami O; van Helvoort, Ardy; Gosker, Harry R; Schols, Annemie MWJ
Abstract : Introduction: Physical and mental health are often affected in chronic obstructive pulmonary disease (COPD) adversely affecting disease course and quality of life. Abnormalities in whole body and cellular energy metabolism, dietary and plasma nutrient status and intestinal permeability have been well established in these patients as systemic determinants of functional decline and underexplored treatable traits. The aim of this study is to investigate the efficacy of 1 year targeted nutrient supplementation on physical activity level and health-related quality of life in patients with COPD. Methods and analysis: This study is a single-centre randomised, placebo-controlled, double-blind trial in 166 patients with COPD recruited from multiple hospitals in the Netherlands. The intervention group will receive a multinutrient supplement, including vitamin D, tryptophan, long-chain polyunsaturated fatty acids and prebiotic dietary fibres as main components (94 kCal per daily dose). The control group will receive an isocaloric isonitrogenous placebo. Both groups will ingest one portion per day for at least 12 months and will additionally receive counselling on healthy lifestyle and medical adherence over the course of the study. Coprimary outcomes are physical activity assessed by triaxial accelerometry and health-related quality of life measured by the EuroQol-5 dimensions questionnaire. Secondary outcomes are cognitive function, psychological well-being, physical performance, patient-reported outcomes and the metabolic profile assessed by body composition, systemic inflammation, plasma nutrient levels, intestinal integrity and microbiome composition. Outcomes will be measured at baseline and after 12 months of supplementation. In case patients are hospitalised for a COPD exacerbation, a subset outcome panel will be measured during a 4-week recovery period after hospitalisation. Ethics and dissemination: This study was approved by the local Ethics Committee of Maastricht University. Subjects will be included after written informed consent is provided. Study outcomes will be disseminated through presentations at (inter)national conferences and through peer-reviewed journals. Trial registration: NCT03807310 .